2002
DOI: 10.1074/jbc.m109916200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Human RAD51 Protein

Abstract: Ammonium sulfate plus spermidine decreased the affinity of hRAD51 for ADP substantially (ϳ10-fold) and ATP modestly (ϳ3-fold). Our results suggest that ATP binding is not rate-limiting but that the inability to sustain an active nucleoprotein filament probably restricts the hRAD51 ATPase.Walker A/B nucleotide binding motifs are conserved in all members of the RecA family, which includes hRAD51 1 and several other human homologs (1, 2). RecA and its homologs belong to a larger more distantly related family of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
(46 reference statements)
6
19
0
Order By: Relevance
“…Therefore, we concluded that accumulation of the inactive hRad51-ADP-ssDNA filament was caused by slow dissociation of ADP, the product of ATP hydrolysis. This conclusion is in accord with the report of Fishel and coworkers (35) that ADP dissociation is the rate-limiting step of ATP hydrolysis by hRad51 protein. In contrast, in the presence of Ca 2ϩ , the filament remains in an active hRad51-ATP-ssDNA form; the amount of protein-bound ADP did not exceed 3-4% after 30 min of incubation (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Therefore, we concluded that accumulation of the inactive hRad51-ADP-ssDNA filament was caused by slow dissociation of ADP, the product of ATP hydrolysis. This conclusion is in accord with the report of Fishel and coworkers (35) that ADP dissociation is the rate-limiting step of ATP hydrolysis by hRad51 protein. In contrast, in the presence of Ca 2ϩ , the filament remains in an active hRad51-ATP-ssDNA form; the amount of protein-bound ADP did not exceed 3-4% after 30 min of incubation (Fig.…”
Section: Resultssupporting
confidence: 82%
“…1E). In agreement with previous studies, we observed strong cross-linking of ATP to hRAD51 (21) and negligible cross-linking of ATP to hXRCC2 (Fig. 1E).…”
Section: Resultssupporting
confidence: 82%
“…hRAD51 (1 M) was incubated at 37°C for 60 min in the presence or absence of hXRCC2 (1 M) or DNA (6 M nt or bp) with the indicated amount of ADP. Bound ADP was determined as described previously (21). ϫ, hXRCC2 in the presence or absence of DNA; E, hRAD51 alone; Ⅺ, hRAD51 alone with X174 ssDNA; ‚, hRAD51 alone with X174 dsDNA RFI; q, hRAD51 plus hXRCC2; f, hRAD51 plus hXRCC2 with X174 ssDNA; OE, hRAD51 plus hXRCC2 with X174 dsDNA RFI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations